"I Knew I Wouldn't be Well Remunerated Before my 30s": Professional Transition in French Journalism. (21st April 2022) - Pereira, Fábio Henrique
ABSTRACT: This article analyzes digital journalists and their entry into French journalism. It combines labor market data with a description of journalistic careers. The study explores the choices made by online journalists in a scenario where employment is decreasing and uncertainties about the future are growing. In order to deal with this situation, French journalists have developed a set of strategies (increased training, more pre-professional experiences, developing skills in digital journalism, and international coverage) that help mitigate the uncertainty around entering the profession. At the same time, the choice to become a journalist in an adverse scenario such as this shows a strong commitment to journalism and a strong adherence to a set of relatively stable features of identity discourse.